Feed value of Gliricidia fodder salt for sheep - Cirne, Luís Gabriel Alves; Baroni, Marly Rosa; De Oliveira, Gabriel Jorge Carneiro; Jaeger, Soraya Maria Palma Luz; Bagaldo, Adriana Regina; De Oliveira, Paulo Andrade; Oliveira, Ronaldo Lopes; Da Silva Lêdo, Carlos Alberto; Barbosa, José Carlos [UNESP]; De Carvalho, Gleidson Giordano Pinto (Universidade Estadual de Londrina, 2016)
This experiment aimed to evaluate the effect of supplementation with Gliricidia fodder salt on intake, nutrient digestibility, and feeding behavior of lambs. Twenty-five Santa Inês crossbred male sheep at approximately 180 days of age, with an average live weight of 25 kg, were confined in individual 1-m2 stalls and distributed in a randomized complete design with five treatments and five replications. Treatments consisted of 0 (1,000 g/kg-1 NaCl), 930, 950, 970, and 990 g/kg-1 inclusion of Gliricidia hay (70, 50, 30, and 10 g/kg-1 NaCl in the formulation of the fodder salt, respectively). The animals were fed ground Tifton-85 (Cynodon spp.) hay, ground fodder salt and or mineral salt, and water ad libitum, at 07h00 and 17h00. Intakes of dry matter, mineral matter, organic matter, crude protein, ether extract, and neutral detergent fiber were influenced (P<0.05) by supplementation with Gliricidia fodder salt. Crude protein intake increased linearly (P<0.01), while mineral-salt intake decreased linearly (P<0.01) as the levels of Gliricidia hay in the fodder salt were increased. There was no difference (P>0.05) in nutrient digestibility due to supplementation. Rumination time and number of cuds ruminated per day decreased (P<0.05), whereas rumination chews per cud increased (P<0.05). Feed and rumination efficiencies (g DM and NDF h-1) increased (P<0.01) with supplementation, and so did the rumination efficiency (P<0.01) expressed in g DM and NDF cud-1. Supplementation with Gliricidia fodder salt increases nutrient intake and positively changes the feeding behavior of lambs.
Keywords: Alternative feed; Digestibility; Ethology; Intake; Supplementation